Investigating the listening and transcription performance in court: experiences from stenographers in Philippine courtrooms - Etulle, Richemyll Dave; Moslares, Fatima Riegnelle; Pacad, Eve Zary Jamie; Odullo, John Lawrence; Nacionales, Joseph; Claridad, Norberto (Yayasan Mitra Persada Nusantara, 2023)
Stenographers are essential figures in a country’s justice system; they are tagged as “silent superheroes” due to their demanding profession of creating official transcripts in legal proceedings by converting “spoken word to text” (Ridoloso, 2023). Stenographers' listening and transcribing accuracy is critical in assuring the dependability and fairness of court processes. Proficiency of the listener does not equate to having a stable listening comprehension all the time, they still encounter challenges in listening. A total of twelve (12) stenographers from different municipal and provincial trial courtrooms within Eastern Visayas were interviewed. Using qualitative research through Interpretative Phenomenological Analysis (IPA), the present study examined the key factors that affect the listening and transcription performance of court stenographers, including how they manage these factors. Using thematic analysis, the participants identified the following key factors that affect their listening and transcription performance: linguistic and cognitive barriers, external and clarity barriers, and challenges in the legal context. The participants likewise revealed that they manage the following challenges through (1) effective courtroom communication and practices; (2) enhancing transcription accuracy with technology and collaboration; and (3) optimizing stenography practices in the legal field. By understanding and addressing these factors, stenographers can enhance their overall performance and contribute to a more effective and efficient justice system.